Soybean Oil Degumming by Immobilized Phospholipase A1 - Redha Kernani; Abdelhamid Boukerroui (Iranian Journal of Chemistry & Chemical Engineering, 2018)
In the present study, we investigated the ability of an immobilized phospholipase A1 (PLA1) in degumming of soybean oil. The enzyme was immobilized by simple adsorption on bentonite without any further modification. The free and immobilized PLA1 were characterized by Fourier Transform InfraRed (FT-IR) spectroscopy and X-Ray Diffraction (XRD). The immobilization of PLA1 lowered the Energy of Activation (EA) from 155.64 to 27.13 kJ/mol, resulting in higher catalytic efficiency of PLA1. Thermal stability of the immobilized enzyme was found to be higher compared to free PLA1. Moreover, under the condition of pH 5.5 and T = 50 °C, the phosphorus content was reduced to less than 10 ppm after 4-5 h for free PLA1 and after 7 h for immobilized PLA1.